(untitled) (Contemporary Journal of Social Science Review, 2025)
This study is about the poetry of the renowned English poet William Wordsworth. Wordsworth wrote many types of poetry. He wrote elegiac, narrative, rustic, lyrical, philosophical, and mystic poetry. This study will critically analyse the tinge of nature, spiritually and transcendence. The poet uses it as a facilitator for a humanoid transcendental experience. Reliance on spirituality enhances the expression of human emotions. This study will decode the multi-layered impact of the mystic poetry of Wordsworth and the role of nature. Wordsworth’s twisted words and his personal experiences with nature will be seen in this research. Multi-layered impressions of nature will be delved into critically. Wordsworth’s poetry is thoroughly embedded with his intuition, diction, and concept of pantheism. The goal of this study is to determine the intervening role of transcendence vibes in interpreting human intuition. This research will examine how nature and its transcendental experience meet the true spirit of the poet’s inner thoughts. There is a chance to observe deeply abstract feelings. The study will evaluate the impact of spirituality and mystic vibes in the poetry of William Wordsworth. A qualitative research mode will be used. The phenomenological approach and hermeneutic theory will be considered. It will indicate the problems with the denotative and connotative enhancement of meanings. Thus, it will highlight the comprehensive outlook on which factors are left unconsidered and how they should be considered. The researcher will use a survey method to collect data from the study’s universe. The researcher will bear in mind the phenomenological approach and the new critical theory to interpret the selected data. This relevant treatment will investigate the context and text from the universe of this study. Open-ended questionnaires, interviews and survey techniques will be used to analyse the data. Relevant poems according to the research questions will be selected to be examined through the unique lenses of the mixed-method technique. A convenient sampling technique and survey will be used by the researcher to collect the data.